ESTRATEGIAS LÚDICAS EN EL APRENDIZAJE DE OPERACIONES DE NÚMEROS ENTEROS EN ESTUDIANTES DE OCTAVO AÑO DE EDUCACIÓN GENERAL BÁSICA PARALELO “A” DE LA UNIDAD EDUCATIVA “RIOBAMBA” EN EL PERIODO SEPTIEMBRE 2019 – FEBRERO 2020 - Garay Avecillas, Geovanny Fernando (2020)
Current education requires constant innovations in the teaching-learning process; it is essential to use several strategies, including playful strategies that allow creating a pleasant and enjoyable environment for both the student and the teacher. This research aims to determine the use of recreational strategies in the learning of operations of integers, in students of the 8th year of Basic General Education of the Unidad Educativa "Riobamba," in the period September 2019 - February 2020. The population involved in this research was 35 students from the mentioned school. This research work has a non-experimental design, variables were not manipulated, and the facts were observed as presented in their context. The Microsoft Office Excel software package and techniques present in the descriptive statistics were used for data processing. From the study carried out, it was observed that in the group of students that was used for research, there is no application of playful strategies by the teacher, which influences in a certain way the students' learning.